Pemberdayaan Ibu Rumah Tangga Melalui Pembentukan Entrepreneur Home Care (Pelatihan Totok Wajah dan Marketing Digital) Desa Makamhaji Kecamatan Kartasura Kabupaten: Empowering Housewives Through the Formation of Home Care Entrepreneurs (Face Acupressure and Digital Marketing Training) Makamhaji Village, Kartasura District, Sukoharjo Regency - Prihatini, Prima; Devi, Anita Oktaviana Trisna; Khusnuliawati, Hardika (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The post-pandemic conditions that have hit the country since March 2020 require people to think more creatively to move the wheels of the family economy. Especially as a housewife who plays a central role in the family, to support the family economy a housewife must have the ability or creativity, especially in the field of creative industry-based entrepreneurship. Through this community service activity the aim is 1) to empower groups of productive age housewives who desire to become an entrepreneur through entrepreneurial socialization; 2) to build talent for creative industry expertise in acupressure skills; 3) to increase the ability to use information technology as a marketing medium (digital marketing) for face-to-face home care by housewives affected by Covid-19 in Dukuh Gobayan; 4) increase knowledge and skills in the field of beauty, especially facial acupressure. The output of this program is a facial acupressure video tutorial. The results of this community service activity are that housewives have an entrepreneurial spirit, can use information technology as a marketing tool, and have acupressure skills.